Effect of transesterification temperature and time on yield and calorific value of biodiesel from refined fat of chicken - Arteaga, Hubert (2010)
The main objective of this research was to determine through the response surface methodology conditions of temperature and time of transesterification which could achieve the higher yield and calorific value in the biodiesel obtained. We used the Central Composite Rotational Design type 22 +2*2, including 4 repetitions at the central point. Chicken fat passed through refining processes, esterification and transesterification weather conditions and temperature of each experiment. The best conditions of temperature were between 50 and 70 oC and time of transesterification between 60 and 120 min, we have obtained an average yield of 94.5% and calorific value in the biodiesel obtained from 40.2 MJ / Kg. We conclude that using the temperature of 56 oC and time of 108.4 minutes,biodiesel is obtained with characteristics required by the ASTM D6751-07, EN 14214 and NTP 321.003.2005standards.